Influences of the unsymmetrical bending on behaviour of structural members with a restrained lateral deflection - Zhang, Zhongwen (2023)
As reinforced concrete (RC) walls with different principal bending axes are connected by the floor diaphragms, unsymmetrical bending is frequently expected for structural members in resisting the lateral loads. In these cases, a portion of lateral reaction forces is anticipated to be perpendicular to the lateral deflection of the members which causes shear deformation and additional curvature perpendicular to the loading plane. This paper investigates these out-of-plane deformations and curvatures and their influences. Magnitude of these shear deformations and curvatures are investigated with experimental data and a theoretical solution. The results confirm that the out-of-plane curvature is related with disproportional shear and flexural stiffness of the wall in different principal bending directions and can account for a significant portion of the in-plane curvature. The curvature could introduce significantly higher strain and render the member more vulnerable to out-of-plane buckling. Methods for modelling the curvature in structural system are proposed based on nonlinear fibre element model.